Study of coercive measures in prisons and secure psychiatric hospitals: the views of inmates and caregivers - A. Runte-Geidel; E. Girela; Á. López; F. Ruiz; F. Torres-González (Sociedad Española de Sanidad Penitenciaria, 2014)
Aim: The aim of the study was to ascertain the opinions of both inmates and staff of prison establishments about the use of coercive measures justified for clinical reasons for people with mental health problems and about the need to create protocols to regulate the application of these measures. Method: These opinions were gathered in a Qualitative Study with Focus Groups (prison inmates and prison staff) from the Granada Penitentiary Centre and the Alicante Penitentiary Psychiatric Hospital, both in Spain. Results: The results showed that forced medication is the most commonly used coercive measure in these institutions. The inmates did not understand and rejected the use of this measure, above all because they were poorly informed about their illness and the medication required to treat it. The staff however defended the benefits of psychiatric medicine, even when administered without the patient's consent. Conclusions: Both inmates and staff agreed that it would be useful to have a protocol regulating the use of coercive measures. The study has also identified a number of important factors that could help to reduce the need for coercive measures or make their use unnecessary.